The Influence of Marketing Mix on Revisit Intention to Mapaddegat Beach, Mentawai Islands: Pengaruh Marketing Mix Terhadap Revisit Intention Ke Pantai Mapaddegat Kepulauan Mentawai - jumiatul mulya; Puspa Leni; Maria Julianti (International Journal of Management and Business (IJMB), 2023)
This research aims to determine the influence of the marketing mix (product, price, promotion, location, people, process, physical evidence, public relations, and power) on revisit intention at the Mapaddegat Beach tourist attraction, Mentawai Islands Regency. The population in this study were people who visited Mapaddegat Beach, Mentawai Islands Regency, totaling 96 people. The data analysis technique is multiple linear regression analysis. The results of the research are that products, promotions, physical items and public relations have a positive and significant effect on revisit intention at the Mapaddegat tourist attraction in the Mentawai Islands. Price has a positive and insignificant effect on revisit intention at the Mapaddegat tourist attraction in the Mentawai Islands. Places and people have a negative and significant effect on revisit intention at the Mapaddegat tourist attraction in the Mentawai Islands. Process and power have an insignificant negative effect on revisit intention at the Mapaddegat tourist attraction in the Mentawai Islands.